Pengembangan Media Pembelajaran Ular Tangga Berbasis Genially Mata Pelajaran Pendidikan Pancasila di Sekolah Dasar - Yuanta, Friendha; Partika, Neta Tabhita; Okatavianti, Pungki Dwi; Hanantha Murty, Tantri Inggrit Galuh; Kurnyawan, Achmad Very; Noorwinanda, M. Navis Roihan Daru (ALACRITY : Journal of Education, 2025)
The development of digital technology has made a significant contribution to the world of education, including in the development of learning media. Web Genially is one of the popular media used in learning because it can increase student engagement and motivation to learn. The purpose of this study was to determine the feasibility and effectiveness of developing snakes and ladders learning media for fourth grade elementary school students. The development of the research used the research and development method or Research and Development (R&D). The ADDIE development model with 5 stages, namely: analysis, design, development, implementation, evaluation. Data collection techniques in the study through observation, documentation, and testing. This Web Genially snakes and ladders learning media was validated by material experts, media experts, and limited trials. The implementation of the trial on fourth grade elementary school students, with the results of the implementation of the snakes and ladders game learning media, student learning motivation increased by 66.7% in the aspects of learning activity and learning enthusiasm, while the aspect of student learning motivation interest increased by 70%. Meanwhile, student learning outcomes increased by 40% from 55% of students who achieved scores below the KKM (minimum completion criteria) to 100% of all students achieving scores above the KKM (minimum completion criteria).